Vilnius Transcript of the “Chronicle of the Lithuanian Grand Princes” - Linguistic Features and Structure - Морозова, Н. (Kalbotyra, 1997)
The article is devoted to the pecularities of the language of the Vilnius transcript of the “Chronicle of the Lithuanian Grand Princes”. Particular attention is paid to the description of the orphographical and morphological variants. The work shows that in this text there are linguistic variants of different origin: the orphographical variants belong to the hand of the last copyist, the morphological variants can be explained by the compilation of the chronicle.